Health expenditure effects on selected health outcomes in ASEAN tiger cub economies - Muhd Naqiyuddin, Misran (2021)
Health expenditure levels in the ASEAN region remains relatively low compared to OECD or world average. As ASEAN thrives to become a dominant economic bloc, major economic players such as the Tiger Cub economies are still struggling to improve health expenditure levels due to political and fiscal constraints. This study aims at investigating the impact of health expenditure levels among ASEAN Tiger Cub economies (Malaysia, Indonesia, Thailand, Philippines and Vietnam) on selected population health outcomes indicator. Data are extracted from the World Bank reports from the year 2000 to 2018.The result indicates that health expenditures significantly influence infant (IMR) and under-5 mortality rate (UMR) but not life expectancy at birth (LEB), while per capita income (pcINC) significantly influences LEB but not IMR or UMR. This study adds to the collection of mixed findings, different from most past literatures that cited significant effect of both health expenditures and per capita income. This finding is important in fostering the understanding of health systems, with emphasis on the discussion of ASEAN’s structural and socioeconomic contexts to explain the results.